Analisis Manajemen Laba Sebagai Variabel Mediasi Dalam Penerapan Good Corporate Governance Dan Corporate Social Responsibility Terhadap Kinerja Keuangan Perusahaan - Heni Nurbayani; Nor Norisanti; Acep Samsudin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The research was aimed at determining direct and indirect influence of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), and Profit Management as mediators towards Company Financial Performance. The data used in the research were in terms of secondary data taken from the state-owned enterprises (BUMN) registered in the Indonesia Stock Exchange in 2018 period. The data were analyzed using Partial Least Square (PLS) with the help of software SmartPLS 3. The results of the research show that GCG has no influence on Profit Management; CSR has a influence on Profit Management; and, Profit Management has a influence on Company Financial Performance. The results also show that Profit Management does not mediate the influence of GCG toward Company Financial Performance, but Profit Management fully mediates the influence of CSR toward Company Financial Perfromance. Keywords : Good Corporate Governance, Corporate Social Responsibility, Profit Management, Company Financial Performance